Right Heart and Pulmonary Vessels Structure and Function. (19th September 2014) - D'Alto, Michele; Scognamiglio, Giancarlo; Dimopoulos, Kostantinos; Bossone, Eduardo; Vizza, Dario; Romeo, Emanuele; Vonk‐Noordergraaf, Anton; Gaine, Sean; Peacock, Andrew; Naeije, Robert
Abstract : The right ventricle (RV) can be described in terms of 3 components: the inlet, the apex, and the infundibulum. In the normal adult, the RV shows an arrangement suited for pumping blood against low resistance, with a mass about one sixth that of left ventricle (LV) mass, and a larger volume than the LV. The RV is able to manage a progressive increase in the afterload by increasing contractility and remodeling. The gold standard measurement of contractility is maximal elastance (Emax), or the ratio between end‐systolic pressure (ESP) and end‐systolic volume (ESV), and the best measurement of afterload is arterial elastance (Ea), or the ratio between ESP and stroke volume (SV). The ratio Emax/Ea defines RV‐arterial coupling. The optimal energy transfer from the RV to the pulmonary circulation is measured at Emax/Ea ratios of 1.5–2. In the presence of pulmonary hypertension, the SV/ESV ratio may be an acceptable surrogate of Emax/Ea. The right atrium (RA) has 3 anatomical components: the appendage, the venous part, and the vestibule. It is a dynamic structure having different functions: reservoir, conduit, and booster pump function. In case of increased afterload, the RA is enlarged, denoting high RA pressure, as a consequence of elevated RV diastolic pressure. RA area is a strong predictor of adverse clinical outcome in pulmonary arterial hypertension. In patients with severe pulmonary hypertension, in several congenital heart diseases, and in Eisenmenger syndrome, symptoms and prognosis are greatly dependent on RV function and its ability to adapt to a chronic increase in afterload.